2014
DOI: 10.1186/1471-2164-15-326
|View full text |Cite
|
Sign up to set email alerts
|

Deep-sequencing transcriptome analysis of low temperature perception in a desert tree, Populus euphratica

Abstract: BackgroundCompared with other Populus species, Populus euphratica Oliv. exhibits better tolerance to abiotic stress, especially those involving extreme temperatures. However, little is known about gene regulation and signaling pathways involved in low temperature stress responses in this species. Recent development of Illumina/Solexa-based deep-sequencing technologies has accelerated the study of global transcription profiling under specific conditions. To understand the gene network controlling low temperatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
60
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 63 publications
(68 citation statements)
references
References 72 publications
7
60
0
Order By: Relevance
“…The functions of the Primer ALS U20 KEL U21 GZ U25 YJ U26 NMH U31 BC U31 AKS U36 SY U20+U21+U25+U26+U31+U36+D1 GEM U20+U21+U25+U26+U31+U36+D1+U25 unigenes were classified by COG and GO, and the metabolic pathways were assigned using the KEGG database. The GO classification analysis showed that the predominant terms of metabolic and cellular processes in biological process were similar to those of numerous other plants, such as Populus euphratica, Boehmeria nivea, and Ipomoea batatas (Wang et al, 2010;Liu et al, 2013;Chen et al, 2014). The predominant term of "single-organism process" is similar to Halogeton glomeratus, another salt-tolerant plant species distributed in arid regions .…”
Section: Characterization Of the Lycium Ruthenicum Transcriptomementioning
confidence: 88%
See 4 more Smart Citations
“…The functions of the Primer ALS U20 KEL U21 GZ U25 YJ U26 NMH U31 BC U31 AKS U36 SY U20+U21+U25+U26+U31+U36+D1 GEM U20+U21+U25+U26+U31+U36+D1+U25 unigenes were classified by COG and GO, and the metabolic pathways were assigned using the KEGG database. The GO classification analysis showed that the predominant terms of metabolic and cellular processes in biological process were similar to those of numerous other plants, such as Populus euphratica, Boehmeria nivea, and Ipomoea batatas (Wang et al, 2010;Liu et al, 2013;Chen et al, 2014). The predominant term of "single-organism process" is similar to Halogeton glomeratus, another salt-tolerant plant species distributed in arid regions .…”
Section: Characterization Of the Lycium Ruthenicum Transcriptomementioning
confidence: 88%
“…The cutoff P-value after correction was 0.05 on a rigorous Bonferroni correction method (Chen et al, 2014). GO terms that meet this standard were defined as significantly enriched GO terms.…”
Section: Gene Expression Analysismentioning
confidence: 99%
See 3 more Smart Citations